PERAN MOTIVASI INTRINSIK DALAM PENGARUH KOMITMEN AFEKTIF DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DISABILITAS - Ignatius Soni Kurniawan Soni (Sains Manajemen : Jurnal Manajemen UNSERA, 2021)
This study aims to determine the effect of affective commitment and competence on employee performance with intrinsic motivation as a mediating variable. The research was conducted on 82 employees with disabilities who work at various companies in Indonesia that use the media Kerjaabilitas.com. The data were collected through a survey with a questionnaire that was distributed online. The findings show that there is a mediating role of intrinsic motivation on the effect of affective commitment on employee performance. It was also found that competence has a direct effect on performance without being mediated by intrinsic motivation.